Strategy in Suriname How do organizations in Suriname Strategize? - Goede, Miguel; Laurens, Roy; Laurens, Roy; Gilaard, Robert; Gilaard, Robert; Rijssel, Robby; Rijssel, Robby; Gefferie, Delano; Gefferie, Delano (Advances in Social Sciences Research Journal, 2018)
Purpose – There are few textbooks available on strategic management based on non-Western practices. This might be a consequence of the lack of studies on strategic management in these countries. The purpose of this article is to describe how organizations in Suriname strategize. Methodology – For this study a brief literature review was conducted, a survey was held and the results were discussed with faculty and students of Anton de Kom, University of Suriname. Findings – Organizations in Suriname do strategize. The economy is the most important factor organizations take into account. The factor that is taken least into account is the ecology. Other factors that are important are social. The multicultural society is taken into account. The political factors, surprisingly, score relatively low. Originality – The paper contributes to the understanding of strategizing by Suriname’s organization and other Caribbean Small Island Developing States (SIDS). Conclusions – Organizations in Suriname do strategize. The economy is the most important factor organizations take into account. The factor that is taken least into account is the ecology.